(untitled) (Research, Society and Development, 2023)
The present work addresses the care of patients assisted by the pharmaceutical public service, aimed at the guidance, control and prevention of injuries and irrational use of medicines, proposing to analyze the user’s expectations before the pharmaceutical consultation and after the completion of the service. This article aims to demonstrate and analyze the quality of care in a pharmaceutical office at the Basic Health Unit (BHU), analyzing expectations and perceptions about it. The research was carried out in a basic health unit, where the SERVQUAL instrument was applied, which consists of a form used to measure the quality of a service, based on the user’s responses before and after the experience with it, in this case treating of the pharmaceutical service. It is, therefore, an investigative, exploratory and descriptive study with a qualitative and quantitative approach. 102 patients were interviewed, of which 81% were women, with the predominant age group being between 41-60 years. Assessment of the dimensions contemplated in the form allowed viewing an expectation and perception of the service as positive by the users, with only a few points of improvement being identified in relation to the physical space and alternative therapeutic options, facts that would be linked to the relatively recent implementation of the service. Therefore, it is concluded that the provision of pharmaceutical services was well evaluated by users, which shows the quality of care provided by the professionals who work there. The importance of this service as a tool for promoting health and strengthening the performance of the clinical pharmacist in primary care is also highlighted.